Representaciones de la actriz y discursos de género en la cultura visual del Romanticismo español - Sandra Gomez Todó (Cuadernos de Ilustración y Romanticismo)
This study explores the redefinition of the professional actress’s identity as a «lady of the stage» in the context of Spanish romantic theatre, focusing on the role played by visual culture in such a process. In the context of the different social circumstances and gender discourses that contributed to the actress’s new social identity, we shall explore how both print culture and portraiture acted as vehicles for the definition and dissemination of the new ideas surrounding this figure.